The need for cultural contextualization in establishing psychological wellness or illness (2010)
Even though the wellbeing literature in psychology is fairly massive, earlier attempts at defining the term have failed to emphasize the pertinence of cultural factors in obtaining a more socially appropriate definition of the term. Hitherto, diagnostic manuals and authors in the area of mental health have been largely driven by medically related models as backgrounds in giving explanations in the area of psychological wellbeing. However, many societies (with their pre-historic values and precepts) had long existing frameworks for establishing psychological health or illness before the advent of current nosological approaches. While it is inappropriate to question the scientific basis of current theories, advancing knowledge within the vicissitudes of our historical past in the context of newer information require the adoption of current gains in scientific trails formation of the area of psychological health; considering peculiar traditional perception of mental health and illness across cultures. This paper attempts to illustrate the relevance of culture and sub-cultural practices in defining the concept of psychological well being, yet appreciating the need to situate these within the' global definition of psychological health. When this is adopted by psychologists and other mental health practitioners, establishing individual and group norms on the mental health-illness continuum will be more society and context specific. The divergence will also yield broader explanations to the existing dogmas in diagnostic criteria in mental health literature. With this in view, the discipline of psychology will be adding value to evidence based assessment and diagnosis, strengthening the insistence on reliability and validity in psychology.